THE IMPACT OF HIGH-INTENSITY INTERVAL TRAINING (HIIT) ON REHABILITATION OUTCOMES FOR POST-STROKE PATIENTS: A COMPARATIVE STUDY - Abdulrahman Melahad Aldahmashi, Farhan Matred Alanazi, Saud Hulayyil Alanazi, Mubarak Sayer Sager Alanazi, Ayed Hamed Ayed Alonquod, Sultan Farhan Al Ruwaili (Chelonian Research Foundation, 2022)
Background: Stroke is a leading cause of disability worldwide, and effective rehabilitation strategies are crucial for improving functional outcomes and quality of life in post-stroke patients. High-intensity interval training (HIIT) has emerged as a promising approach to enhance cardiovascular fitness and motor function in various populations, including stroke survivors. Objective: This study aimed to compare the effects of HIIT versus conventional rehabilitation on functional outcomes, cardiovascular fitness, and quality of life in post-stroke patients. Methods: A randomized controlled trial was conducted with 60 post-stroke patients (30 in each group). The HIIT group underwent a 12-week program consisting of high-intensity cycling intervals, while the control group received conventional rehabilitation. Outcome measures included the Fugl-Meyer Assessment (FMA), 6-Minute Walk Test (6MWT), Stroke Impact Scale (SIS), and peak oxygen uptake (VO2peak). Assessments were performed at baseline, 6 weeks, and 12 weeks. Results: Both groups showed significant improvements in all outcome measures over time (p<0.05). However, the HIIT group demonstrated significantly greater improvements in FMA (p=0.008), 6MWT (p=0.002), SIS (p=0.015), and VO2peak (p<0.001) compared to the control group at 12 weeks. Conclusion: HIIT appears to be a more effective rehabilitation strategy than conventional therapy for improving functional outcomes, cardiovascular fitness, and quality of life in post-stroke patients. Incorporating HIIT into stroke rehabilitation programs may lead to better patient outcomes and faster recovery.